Managing intense emotions and overcoming self-destructive habits a self-help manual - Bell, Lorraine (Brunner-Routledge, 2003)
Managing Intense Emotions and Overcoming Self-Destructive Habits is a self-help manual for people who would meet the diagnosis of 'emotionally unstable', or 'borderline personality disorder' (BPD), outlining a brief intervention which is based on a model of treatment known to be effective for other conditions, such as anxiety, depression and bulimia." "The manual describes the problem areas, the skills needed to overcome them and how these skills can be developed. It is designed to be used with the help of professional mental health staff, ideally in a group, with individual sessions to support and coach the person in the application of the skills taught." "Borderline personality disorder is a complex and challenging condition. This manual aims to explain the problems experienced by people who may be given this diagnosis in a way that clients and staff can easily understand. It will be essential reading for people with BPD and professionals involved in their care - psychologists, psychiatric nurses, psychiatrists and occupational therapists.